A creative model of entrepreneurship learning to improve self-efficacy, entrepreneurial intention, and student achievement - Hutasuhut, Saidun; Thamrin, Thamrin; Ridwan, Muhammad (Creativity Studies, 2023)
This study aims to produce a valid, practical and effective model of entrepreneurial learning to achieve human resources with high level of knowledge and entrepreneurial spirit, and it uses Albert Bandura’s social cognitive theory and self-efficacy. Self-efficacy is someone’s belief or confidence to implement a variety of activities based on the knowledge, experience and skills possessed. The study was conducted at State University of Medan, Indonesia and some small companies. The population was the whole 2016 classes studying entrepreneurship at State University of Medan and all the small businesses in Medan, North Sumatra, Indonesia. Four classes in the Faculty of Economics and four companies were selected by purposive random sampling. The development research method used: 1) initial investigation, 2) design, 3) realization (construction), and 4) testing, evaluation, revision. The sample was used for the application and experimentation of the learning model, and the companies were for students’ internship/observation. The quality of the models was assessed using the indicators of validity, practicality, and effectiveness. The validity was tested by experts of instructional model. The effectiveness was measured by comparing 1) self-efficacy, 2) entrepreneurial intention, and 3) the improvement of learning achievement by Student’s t-test. The research findings proved that the application of business-based entrepreneurial learning model can positively and significantly improve students’ entrepreneurial intention, but it cannot improve the academic achievement of students.